Impact of Work Environment to the Productivity of Employee at Public Employment Service Office in Quezon City: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Every individual knows that there are things in our environment that might cause positiveand negative impacts that affect our duties as an office worker. This is how researchersended up studying the Impacts of the work environment on the productivity of employees atthe Public Employment Service Office in Quezon City. PESO is a government office thathelps its community to get a job under any circumstances.The result of the study revealed the impact of the office environment on the productivity ofemployees in PESO in terms of the cited variables: 2.1 Workplace Ambiance- theemployee’s motive to work effectively if they have a good workplace environment. 2.2Physical Layout- the employees who have their own workplace space can be productive. 2.3Office Equipment - Having good quality office supplies and equipment, employees can workefficiently and produce quality work. 2.4 Ergonomics- The ergonomically designedequipment used by the workers makes them feel comfortable, which contributes to theirability to perform their daily duties. 2.5 Workspace- the employees feel comfortable having aphysical workplace setting to do their tasks smoothly.The results of the gathered data conclude that environment, such as Workplace Ambiance,Office Layout, Office Equipment, Ergonomics, and Workspace, has a great impact when itcomes to the quality and level of productivity of employees as a part of the officeenvironment. This might have a positive and negative impact on the productivity ofemployees. Having a positive work environment is essential for any organization to succeed.It encourages employees to be more productive, creative, and motivated in work.
Keywords: Business Administration